Comparative studies on the physical properties of fibres of Bt and non-Bt cottons at various stages of growth - YADAV, A; HUSSAIN, G F S; NACHANE, R P (The Indian Journal of Agricultural Sciences, 2014)
The comparative studies pertaining to Bt and non-Bt cottons assessing quality performances of fibres for 2004–05 and 2005–06 was done from the data collected at various stages of crop growth at Athawa Agricultural Research Farm in Surat (Gujarat). Two varieties of Bt cottons, viz. RECH-2 and MECH-184 and their non-Bt counterparts (RECH-2 and MECH-184) were selected for the study. Physical parameters of fibers such as micronaire, 2.5% span length, tenacity, maturity ratio, neps count/g and immature fiber content (IFC%) were determined by standard procedures. There was no difference among micronaire, 2.5% span length, immature fibre content, neps/g and maturity ratio at the final stage of fibre development. However, the tenacity encountered some change in the final stage of fibre development.